ANALYSIS OF FINANCING OF EXPENDITURES ON SOCIAL SECURITY AND SOCIAL PROTECTION OF CITIZENS OF THE REPUBLIC OF KAZAKHSTAN - Tokseitova Asel Sembaevna; Esenova Gulmira Zheksenovna (Academic Journal of Physical and Chemical Sciences, 2020)
The actualization of social protection of the population consists in the fact that the concept of “social protection” is associated with the concept of “social care” of the state, when individual assistance to a person, groups of people organized by professionally trained people and expressed by the concept of “social work” will have the support of confidence as its ultimate goal man in his strength, his capabilities. That is why in recent years, most specialists of social protection of the population refuse from such a broad, but non-specific concept as "state regulation of the social sphere", and use the term "social support of the population by the state" more and more. The social policy of any state is the most important part of its domestic policy. In the context of Kazakhstan’s transition to sustainable development, the problem of improving the social security system of the population becomes especially acute and relevant. The right to social security of citizens is exercised in practice using a specific organized financial mechanism, which includes a set of interrelated organizational, economic, legislative and other measures.